2012
DOI: 10.1111/j.1740-0929.2012.01030.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of protein disulfide isomerase during maturation of pig oocytes

Abstract: Oocyte maturation in mammals is characterized by a dramatic reorganization of the endoplasmic reticulum (ER). In mice, the ER forms accumulations in the germinal vesicle (GV) stage and distinctive cortical clusters in metaphase II (MII) of the oocyte. Multiple evidence suggests that this ER distribution is important in preparing the oocyte for Ca(2+) oscillations, which trigger oocyte activation at fertilization. In this study, we investigated the time course and illustrated the possible functional role of ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Both proteins reduce oxidative stress and protein misfolding essential for embryo development [39]. PDI/TRX is involved in oocyte maturation, [40] gamete fusion [41] zona hardening and monospermy [42] as well as proliferation preventing inner cell mass apoptosis [43]. Also, addition of exogenous TRX protects against ROS [7].…”
Section: Introductionmentioning
confidence: 99%
“…Both proteins reduce oxidative stress and protein misfolding essential for embryo development [39]. PDI/TRX is involved in oocyte maturation, [40] gamete fusion [41] zona hardening and monospermy [42] as well as proliferation preventing inner cell mass apoptosis [43]. Also, addition of exogenous TRX protects against ROS [7].…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the PKC role on ER distribution, MII oocytes and oocytes activated in the presence or not of PKC inhibitor (BIM 10 µM) were evaluated by immunofluorescence using the antibody anti‐ER‐associated protein, protein disulfide isomerase (PDI). PDI has been successfully used to mark ER organization in oocytes (Ohashi, Hoshino, Tanemura, & Sato, 2013). In MII oocytes, ER was observed throughout the cytoplasm and mainly concentrated at the oocyte cortex (Figure 2, a–c; a′).…”
Section: Resultsmentioning
confidence: 99%
“…PDIs are chaperone molecules advantageous for the viability and immune protection of eggs and early embryos of Pacific oyster, and it is up-accumulated in good quality oyster oocytes [ 19 ]. Previous studies reported that PDIs are involved in oocyte development [ 88 ] and sperm–egg fusion at fertilization [ 89 90 ], suggesting that also sperm–egg interaction are crucial determinants in oocytes quality and developmental success.…”
Section: Discussionmentioning
confidence: 99%